Ibrutinib for bridging to allogeneic hematopoietic cell transplantation in patients with chronic lymphocytic leukemia or mantle cell lymphoma: a study by the EBMT Chronic Malignancies and Lymphoma Working Parties - Dreger, Peter; Dietrich, Sascha (Bone marrow transplantation, 2019)
The aim of this retrospective study was to investigate the safety and efficacy of allogeneic hematopoietic cell transplantation (alloHCT) in patients pre-treated with ibrutinib. Eligible were patients aged >18 years allotransplanted for chronic lymphocytic leukemia (CLL) or mantle cell lymphoma (MCL) after prior exposure to ibrutinib who were registered with the EBMT registry. Seventy patients (CLL 48, MCL 22) were included. At the time of alloHCT, 73% of the patients were ibrutinib responsive. All patients except one engrafted, and acute GVHD grade 2-4 (3-4) was observed in 49% (12%) of 68 evaluable patients. The cumulative incidence of chronic GVHD was 54% 1 year after transplant. In the CLL group, 12-month non-relapse mortality, relapse incidence (RI), progression-free survival (PFS), and overall survival (OS) were 10, 30, 60, and 72%, respectively, and in the MCL group 5, 19, 76, and 86%, respectively. Pre-transplant ibrutinib failure and poor performance status predicted inferior RI, PFS and OS in the CLL group. In conclusion, ibrutinib does not affect the safety of a subsequent alloHCT. While the relatively high post-transplant relapse risk in ibrutinib-exposed patients with CLL deserves further study, in patients with MCL consolidating disease responses to ibrutinib with alloHCT seems to be a promising option.
Gesehen am 14.06.2019
Published online: 4 May 2018